2018
DOI: 10.1002/bin.1525
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of elopement following a latency‐based interview‐informed, synthesized contingency analysis

Abstract: Using a latency measure during a functional analysis of problem behavior increases the brevity of the assessment period and decreases risks resulting from exposure to contexts intended to evoke problem behavior. In addition, latencybased functional analyses may be especially suitable for discrete behaviors such as elopement, which require resetting the environment after each instance of the response. We evaluated a comprehensive assessment and treatment package for the elopement of two children diagnosed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…We are somewhat limited in interpreting similarities in these outcomes with previous CBPD studies due to DRA‐ and DRO‐based thinning procedures often being combined into a single treatment package (e.g., Beaulieu et al, 2018; Hanley et al, 2014; Rose & Beaulieu, 2019) or evaluated individually without comparison (e.g., Boyle et al, 2020; Jessel et al, 2018b; Santiago et al, 2015). Ghaemmaghami et al (2016) included the only other comparative evaluation of CBPD procedures with a single participant, Will, and found that although both reduced problem behavior, the DRA‐based thinning procedure was more effective and improved contextually appropriate behavior.…”
Section: Discussionmentioning
confidence: 78%
“…We are somewhat limited in interpreting similarities in these outcomes with previous CBPD studies due to DRA‐ and DRO‐based thinning procedures often being combined into a single treatment package (e.g., Beaulieu et al, 2018; Hanley et al, 2014; Rose & Beaulieu, 2019) or evaluated individually without comparison (e.g., Boyle et al, 2020; Jessel et al, 2018b; Santiago et al, 2015). Ghaemmaghami et al (2016) included the only other comparative evaluation of CBPD procedures with a single participant, Will, and found that although both reduced problem behavior, the DRA‐based thinning procedure was more effective and improved contextually appropriate behavior.…”
Section: Discussionmentioning
confidence: 78%
“…Our study departed from previous investigations of the IISCA in that we did not teach a functional communication response as an alternative to challenging behavior (cf. Jessel, Ingvarsson, Metras, Kirk, & Whipple, ; Jessel, Ingvarsson, Metras, Whipple, et al, ). However, the IISCA still allowed the experimenters to identify maintaining, functional reinforcers for both participants' transition refusal behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The full IISCA has been shown to be an efficient functional analysis format with large clinical case summaries reporting mean analysis durations of 25 min (Jessel et al, ) and 36 min (Jessel, Ingvarsson, Metras, et al, ). The current study improves on this analytic brevity by reducing the time further to only 5 min.…”
Section: Discussionmentioning
confidence: 99%
“…An important next step would be to conduct and report the entire assessment and treatment process across a large number of consecutive patients who experience this assessment and treatment process. This arrangement has been characterized as a consecutive case series design (Phillips, Iannaccone, Rooker, & Hagopian, ) and has already been shown to support the effectiveness and treatment utility of the full IISCA across child characteristics, contexts, and topographies of problem behavior for 25 consecutive participants (Jessel, Ingvarsson, Metras, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation